Bilateral posterior cervical cages provide biomechanical stability: assessment of stand-alone and supplemental fixation for anterior cervical discectomy and fusion - Voronov, Leonard I (Med Devices (Auckl), 2016)
INTRODUCTION: Supplemental posterior instrumentation has been widely used to enhance stability and improve fusion rates in higher risk patients undergoing anterior cervical discectomy and fusion (ACDF). These typically involve posterior lateral mass or pedicle screw fixation with significant inherent risks and morbidities. More recently, cervical cages placed bilaterally between the facet joints (posterior cervical cages) have been used as a less disruptive alternative for posterior fixation. The purpose of this study was to compare the stability achieved by both posterior cages and ACDF at a single motion segment and determine the stability achieved with posterior cervical cages used as an adjunct to single- and multilevel ACDF. METHODS: Seven cadaveric cervical spine (C2–T1) specimens were tested in the following sequence: intact, C5–C6 bilateral posterior cages, C6–C7 plated ACDF with and without posterior cages, and C3–C5 plated ACDF with and without posterior cages. Range of motion in flexion–extension, lateral bending, and axial rotation was measured for each condition under moment loading up to ±1.5 Nm. RESULTS: All fusion constructs significantly reduced the range of motion compared to intact in flexion–extension, lateral bending, and axial rotation (P<0.05). Similar stability was achieved with bilateral posterior cages and plated ACDF at a single level. Posterior cages, when placed as an adjunct to ACDF, further reduced range of motion in both single- and multilevel constructs (P<0.05). CONCLUSION: The biomechanical effectiveness of bilateral posterior cages in limiting cervical segmental motion is comparable to single-level plated ACDF. Furthermore, supplementation of single- and multilevel ACDF with posterior cervical cages provided a significant increase in stability and therefore may be a potential, minimally disruptive option for supplemental fixation for improving ACDF fusion rates.